Dental screening prior to valve interventions: Should we prepare transcatheter aortic valve replacement candidates for "surgery"?. (1st November 2019) - Carasso, Shemy; Amy, Dalit Porat Ben; Kusniec, Fabio; Ghanim, Diab; Sudarsky, Doron; Kinany, Wadi; Shmuel, Chen; Abu El-Naaj, Imad; Kachel, Erez; Amir, Offer
Abstract: Background: 40% of cases of infective endocarditis (IE) are likely caused by oral bacteria. IE prevalence after transcatheter aortic valve replacement (TAVR) is comparable to IE following surgical prosthetic valve replacement (SVR). Current guidelines recommend pre-operative dental screening for SVR, without specific recommendations regarding TAVR. We aimed to compare oral dental findings in TAVR vs. surgical valve replacement (SVR) candidates and assess the need for routine dental screening and treatment prior to TAVR similar to the SVR patients. Methods: 150 patients (58 TAVR candidates and 92 surgical candidates) were all referred for screening and appropriate treatment before intervention to our Oral medicine team, blinded to the planned interventional type. All patients were scored for oral hygiene and dental findings that required intervention. An oral health score (OHS, general hygiene: 0-good, 1-bad, need for immediate treatment: 0-no, 1-yes, need for future treatment: 0-no, 1-yes) was calculated and compared. Patients were clinically followed for IE for 14 ± 5 months (rage 8–28) post intervention. Results: While candidates for SVR were younger than TAVR (66 + 10 vs. 81 ± 6 respectively, P  < 0.0001), oral-dental findings were similar. OHS was 1.6 for SVR and 1.7 for TAVR candidates, p  = 0.45). Half of patients in either group had findings requiring pre-procedural dental treatment. There were two IE cases during follow-up, one in each group. Conclusion: Oral health and need for pre-procedural dental treatment were not different among candidates for SVR and TAVR. IE preventive oral-dental care seems to be justified in patients undergoing TAVR initially denied SVR due to prohibitive operative risk. Highlights: Guidelines suggest endocarditis prophylaxis should be delivered similarly after all aortic valve replacement procedures Oral hygiene was found to be similar among candidates for transcatheter and surgical aortic valve replacement Pre-procedural oral-dental assessment probably should be similarly addressed as well